Association Between Homocysteine, Frailty and Biomechanical Response of the CNS in NPH-Suspected Patients. Issue 7 (24th March 2022) - Guillotin, Sophie; Vallet, Alexandra; Lorthois, Sylvie; Cestac, Philippe; Schmidt, Eric; Delcourt, Nicolas
Abstract: Frailty is a geriatric syndrome that combines physiological decline, disruptions of homeostatic mechanisms across multiple physiologic systems and thus, strong vulnerability to further pathological stress. Previously, we provided the first evidence that increased risk of poor health outcomes, as quantified by a frailty index (FI), is associated with an alteration of the central nervous system (CNS) biomechanical response to blood pulsatility. In this study, we explored correlation between 14 biological parameters, the CNS elastance coefficient and FI. We included 60 adults (52–92 years) suspected of normal pressure hydrocephalus and presenting with markers of multiple coexisting brain pathologies, including Parkinson disease, Alzheimer disease, and vascular dementia. We showed that the homocysteine (Hcy) level was independently and positively associated with both the FI and the CNS elastance coefficient (adjusted R ² of 10% and 6%). We also demonstrated that creatinine clearance and folate level were independently associated with Hcy level. Based on previous literature results describing the involvement of Hcy in endothelial dysfunction, glial activation, and neurodegeneration, we discuss how Hcy could contribute to the altered biomechanical response of the CNS and frailty.